Study of the acoustic performance of composites made from recycled cellulose acetate and polymer waste. Issue 4 (December 2022) - Maderuelo-Sanz, Rubén; García-Cobos, Francisco José; Sánchez-Delgado, Francisco José
The main objective of this study is to evaluate the acoustic behaviour of composites made by mixing cellulose acetate, from recycled cigarette butts, with polymers such as polyethylene and polypropylene, from recycled plastic containers and surgical masks, respectively. For this purpose, the spectra of the measured sound absorption coefficients and the calculated NRC and SAA indices of samples with thicknesses of 1.5, 3, 4.5, 6 and 7.5 cm are analysed. The results of both experiments reveal that the studied composites present a sound absorption capacity comparable to that of fibre glass and rock wool, being even more efficient for thicknesses greater than 4.5 cm. Moreover, the acoustical properties of the composites are predicted using the Miki model over the frequency range from 100 to 6400 Hz, showing very accurate predictions of the sound absorption spectrum at normal incidence.